Formation of nanocomposite structures based on irradiated nanotubes and metal oxides and investigation of their chemical sensitivity - V. E. Roslikov; E. A. Roslikova; Yu. A. Stenkin; S. N. Povoroznyuk (Омский научный вестник)
Nanocomposite structures based on irradiated Ar + ions of multiwalled carbon nanotubes (MWNTs) and metal oxides (SnOx and TiO2-x) are obtained. By scanning electron microscopy (SEM), it is found that metal oxides uniformly cover MWNTs. The study of electrophysical and gas sensitive properties shows that the resulting test composite structures have a higher sensitivity to the molecules of gases NO2 and H2 S at room temperature than the layers of MWCNs not modified by metal oxides.